European research networks to facilitate drug research in children. Issue 10 (20th September 2020) - Turner, Mark A.; Cheng, Katharine; de Wildt, Saskia; Hildebrand, Heidrun; Attar, Sabah; Rossi, Paolo; Bonifazi, Donato; Ceci, Adriana; Claverol, Joana; Nafria, Begonya; Giaquinto, Carlo
Abstract : Paediatric drug development faces several barriers. These include fragmentation of stakeholders and inconsistent processes during the conduct of research. This review summarises recent efforts to overcome these barriers in Europe. Two exemplar initiatives are described. The European Paediatric Translational Research Infrastructure facilitates preclinical research and other work that underpins clinical trials. conect4children facilitates the design and implementation of clinical trials. Both these initiatives listen to the voices of children and their advocates. Coordination of research needs specific effort that supplements work on science, resources and the policy context. Abstract : European research networks facilitate drug research in children